UNPACKING THE MEANING OF SYMBOLS AND TEXTS FEMALE FIGURE IN THE TRUCK - Pratama, Nicholas Wila Adi; Swandi, I Wayan; Udayana, Anak Agung Gede Bagus; Artadi, I Made Pande (International Journal of Multidisciplinary Research and Literature, 2025)
A common phenomenon from time to time is that you can always find visual aspects on the tailgate of various visual idioms, ranging from images of women, idols, panoramas, words of satire, motivation, and humorous diction. Often the themes depicted are nearby phenomena and events that are “hits” in the community. Then it becomes a habitus that reinforces that the image on the truck bed turns the street into a showcase. The research focus is realized in the objectives of this study; (1) Describing visual data through 5 images in the form of female public figures who are often discussed in the world of entertainment information in Indonesia. (2) Analyzing the visual form of the female public figure is considered to represent the meaning of symbols and texts that can be interpreted. The research method used is descriptive qualitative through a hermeneutic approach to describe the contextual experience of the results of obtaining research data on the female figure on the tailgate. The research procedure was carried out through the process of collecting field data, identifying the results of further observations, literature review, extracting data through primary sources through in-depth interviews with selected sources including; members of the poor truck community, individuals who apply formal authority and local informal actors. The researcher used the principle of Paul Ricouer's Critical Hermeneutics study. The results of the research presented; (1) unfold the interpretation of symbolic meaning, that the tailgate artwork often uses symbols in the medium of expression of the tailgate to describe various social conditions and cultural contexts of everyday life which are an integral part of cultural identity. (2) Analyzing the visual text in specific styles and techniques of art creation to present a characteristic, a hallmark of a period of development of truck visual art and the identity of the truck user or driver